The Global Financial Crisis and Economic Growth: An Analysis of the East Asian Economies - Fang Yin; Xiao Hong; Lin Yao (Pt. Riset Press International, 2023)
Along with more its integrated economy in middle globalization era, crisis finances that occur in a country can with easy spread to countries other and become a global financial disaster in period time which short. On incident sort of this, very strong economic fundamentals important for maintain something country from effect crisis which